Orientin Reduces Myocardial Infarction Size via eNOS/NO Signaling and Thus Mitigates Adverse Cardiac Remodeling - Li, Fangfang; Zong, Jing; Zhang, Hao; Zhang, Peijie; Xu, Luhong; Liang, Kai; Yang, Lu; Yong, Hui; Qian, Wenhao (Frontiers in Pharmacology, 2017)
Orientin is a flavonoid extracted from Chinese traditional herb, Polygonum orientale L. Previous study has reported that orientin protected myocardial from ischemia reperfusion injury. However, whether orientin could protect against cardiac remodeling after myocardial injury remians unclear. The aim of our study is to investigate the effects of orientin in the progression of cardiac remodeling after myocardial infarction (MI). Mice cardiac remodeling model was established by left coronary artery ligation surgery. Experimental groups were as follows: vehicle-sham, orientin-sham, vehicle-MI, and orientin-MI. Animals were treated with vehicle or orientin (40 mg/kg) for 25 days starting 3 days after surgery. After 4 weeks of MI, mice with orientin treatment had decreased mortality and improved cardiac function. Significantly, at 4 weeks post-MI, orientin treatment decreased fibrosis, inflammatory response, and cardiomyocyte apoptosis. Furthermore, orientin treatment attenuated the hypoxia-induced neonatal rat cardiomyocyte (NRCM) apoptosis and increased cell viability. Additionally, orientin supplementation mitigated oxidative stress in remodeling heart tissue and cardiomyocytes exposed to hypoxia. Mechanistically, orientin promotes cardioprotection by activating the eNOS/NO signaling cascades, which was confirmed by eNOS inhibitor (L-NAME) in vitro and vivo. Inhibition of oxidative stress by orientin via eNOS/NO signaling cascades in the heart may represent a potential therapy for cardiac remodeling.